A Novel Approach for the Enumeration of Peripheral Blood Stem Cells Suitable for Transplantation - Winston Costa Pereira; Omar Alsuhaibani; Ghaleb Elyamany; Abdulaziz Al Abdulaaly (Journal of Transplantation)
Stem cells have the capability to proliferate and differentiate into various cells of the body. Few stem cell sources have been approved for transplantation, among them are the hematopoietic progenitor cells which are progenitors of the myeloid and erythroid lineage in the hematopoietic system, that continually provides mature blood cells during the lifespan of the individual. These well-characterized stem cells are clinically relevant in the treatment of diseases such as breast cancer, leukemias, and congenital immunodeficiencies. Peripheral blood stem transplantation is a standard procedure after its first successful transplantation more than 35 years ago. The minimum intended dose of stem cells given to the patient is 2.5×106 –5×106 cells. In this study, we are establishing a correlation between the number of stem cells enumerated and the weight of the patient as a determinant for suitable transplantation. We have established a conversion factor to deliver the required dose of approximately 3×106 stem cells/kg body weight. This will ensure a uniform collection strategy that is sufficient for transplantation irrespective of the weight of the patient. This approach, if incorporated, will lead to a significantly lesser rate of bone marrow transplantation failures as sufficient number of stem cells will ensure engraftment of stem cells.